Cotton WATs Modulate SA Biosynthesis and Local Lignin Deposition Participating in Plant Resistance Against Verticillium dahliae - Tang, Ye; Zhang, Zhennan; Lei, Yu; Hu, Guang; Liu, Jianfen; Hao, Mengyan; Chen, Aimin; Peng, Qingzhong; Wu, Jiahe (Frontiers in Plant Science, 2019)
ABSTRACT Verticillium wilt caused by Verticillium dahliae seriously limits cotton production. It is difficult to control this pathogen damage mainly due to the complexity of the molecular mechanism of plant resistance to V. dahliae. Here, we identified three homologous cotton Walls Are Thin (WAT) genes, which were designated as GhWAT1, GhWAT2, and GhWAT3. The GhWATs were predominantly expressed in the roots, internodes, and hypocotyls and induced by infection with V. dahliae and treatments with indole-3-acetic acid (IAA) and salicylic acid (SA). GhWAT1-, GhWAT2- or GhWAT3-silenced plants showed a comparable phenotype and level of resistance with control plants, but simultaneously silencing three GhWATs (GhWAT123-silenced) inhibited plant growth and increased plant resistance to V. dahliae, indicating that these genes were functionally redundant. In the GhWAT123-silenced plants, the expression of SA related genes were significantly upregulated compared with the control, resulting in an increase of SA level. Moreover, the histochemical analysis showed that xylem development was inhibited in GhWAT123-silenced plants compared with the control. However, lignin deposition increased in the xylem of the GhWAT123-silenced plants than that the control. And there were higher expression levels of lignin synthesis- and lignifications-related genes in the GhWAT123-silenced plants. Collectively, the results showed that GhWATs in triple-silenced plants acts as negative regulators of plant resistance against V. dahliae. The potential mechanism of the WATs functioning in the plant defence can modulate the SA biosynthesis and lignin deposition in the xylem.